(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Understanding the types of tourist attractions in Bangka Belitung is essential for tourism personnel, especially for tourism vocational high school students. This article describes a community service initiative by the International Citra Institute aimed at enhancing tourism knowledge among vocational high school students in Bangka Belitung. The methods used to deliver the material include lectures and group discussions in the classroom. Student capacity-building activities show results as expected. SMKN 3 Pangkalpinang students finally understood the types of tourist attractions owned by Bangka Belitung. They can distinguish and categorise tourist attractions into natural, cultural, and man-made categories. This shows an increase in basic tourism Knowledge among students. This activity is expected to foster the development of competent tourism human resources, enabling them to make a positive contribution to addressing the shortage of tourism resources in Bangka Belitung.